Development of A Model for Strengthening Teacher Capacity Through School Quality Reports at SMP Negeri 2 Telaga - Ansar Ansar; Warni Tune Sumar; Fachrudin Akadji (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research aims to analyze teacher capacity building at State Middle Schools in Telaga District, Gorontalo Regency, focusing on four main aspects: program planning, learning implementation, assessment of student learning outcomes, and development of teacher professional activities. This research uses a quantitative descriptive percentage method, analyzed using descriptive techniques and formula-based calculations, in the sense that each question item in the questionnaire is tabulated to obtain the percentage for each indicator, which is then presented in diagrams and further analyzed using interviews with respondents to support the percentage findings. The research results show that (1) program planning at State Middle Schools in Telaga District, Gorontalo Regency, is in the good category with a percentage of 91%. (2) The implementation of learning at State Middle Schools in Telaga District, Gorontalo Regency, is in the good category with a percentage of 86%. (3) The assessment of learning outcomes at State Middle Schools in Telaga District, Gorontalo Regency, is in the good category with a percentage of 88%. (4) The development of teacher professional activities at State Middle Schools in Telaga District, Gorontalo Regency, is in the good category with a percentage of 84%.